The Advances in Molecular and New Point-of-Care (POC) Diagnosis of Schistosomiasis Pre- and Post-praziquantel Use: In the Pursuit of More Reliable Approaches for Low Endemic and Non-endemic Areas - Cavalcanti, Marta G.; Cunha, Aline Fernandes Araujo; Peralta, José Mauro (Frontiers in Immunology, 2019)
Like soil-transmitted helminth infections, schistosomiasis is an important neglected tropical disease (NTD) related to poverty with a major impact on public health in developing countries. Diagnosis of active infection is crucial for surveillance of controlled or post-elimination schistosomiasis areas. In addition, the use of conventional diagnostic tools in non-exposed populations (such as travelers) results in misdiagnoses in the prepatent period of infection. Also, the accuracy of standard tests applied in low-endemicity areas (LEAs) decreases after several rounds of treatment. We aimed to determine whether it would be necessary to replace schistosomiasis conventional diagnostic tests such as parasitological methods in LEAs. Also, we evaluate the use of new tools in non-endemic areas. Reliable, cheap and easy-to-use diagnostic tools are needed to respond to the demands of a new era of elimination and eradication of schistosomiasis. To this end, molecular diagnosis—including nucleic acid-based assays (loop-mediated isothermal amplification, polymerase chain reaction) and circulating cathodic and anodic antigen detection tests have become promising strategies. In this review, we attempt to address the use of alternative diagnostic tests for active infection detection and drug-monitoring after specific schistosomiasis treatment.